Community Participation in Agrotourism Development in Cibodas Village, Lembang District, West Bandung Regency - Salam, Dicky Arsyul; Wyratama, Marubeni Yusuf; Natasha, Ischa; Pramesthi, Riana Ika; Ahzar, Aimar Achdiatul; Syafitri, Melinda Ade; Novianti, Syifaa (Journal of Tourism, Hospitality and Travel Management, 2023)
Community participation or involvement plays an essential role in developing tourism activities, from planning to implementation. Consequently, community participation plays a part in determining the success factor of tourism development conducted in Cibodas Village, an emerging community-based tourism village in Bandung, Indonesia. This study aims to identify several forms of community participation in developing agrotourism. The descriptive qualitative method is used for the research to collect data by observing, interviewing, and studying existing documentation. The study indicates that the strong relationship among local communities, farmers, and government primarily empowers community participation in Cibodas Village. Although the development of agrotourism in the village still faces challenges due to other farming preferences among the local communities, the farmers' participation in contributing to the development has significantly increased. Agrotourism activities offered by the community and farmers in Cibodas Village are in the form of educational tourism through visiting agricultural land to identify types of plants, learning how to pick and care for plants, and enjoying processed food and drinks from agricultural products.